The Spirit of Compromise Why Governing Demands It and Campaigning Undermines It - Gutmann, Amy (Princeton University Press, 2014)
To govern in a democracy, political leaders have to compromise. When they do not, the result is political paralysis-dramatically demonstrated by the gridlock in Congress in recent years. In The Spirit of Compromise, eminent political thinkers Amy Gutmann and Dennis Thompson show why compromise is so important, what stands in the way of achieving it, and how citizens can make defensible compromises more likely. They urge politicians to focus less on campaigning and more on governing. In a new preface, the authors reflect on the state of compromise in Congress since the book's initial publication. Calling for greater cooperation in contemporary politics, The Spirit of Compromise will interest everyone who cares about making government work better for the good of all
Description based on publisher supplied metadata and other sources
Keywords: Compromise (Ethics) -- United States; Consensus (Social sciences) -- United States; Decision making -- United States; Democracy -- United States; Political planning -- United States; Konsens; Kompromiss; Politische Kultur; Wahlkampf; Politisches Handeln; USA